Tinjauan Yuridis Perjanjian Perdamaian Dalam Penyelesaian Perkara Perdata - Hakim, Adlan Fakhrusy, Mutimatun Ni'ami, S.H., M.Hum, Aristiya Windiana P, S.H., LLM (2015)
Not always a civil dispute must be resolved through litigation in court. Efforts to settle a legal case can be done by means of peace. Basically, in a civil case proceedings, the first thing done by a panel of judges is to reconcile both parties litigant. Because peace itself basically had to end the case. Based on the existence of peace between the two sides that the judge will make a decision in the form of a deed of peace. This study uses normative juridical approach, which is descriptive. Using these types of primary and secondary data. Data collection technique is done by through the study of literature, documentation, questionnaires and interviews. By using qualitative data analysis. It was concluded that that about legal consequences arising from their decision / deed of peace and binding as described above is in conformity with the provisions stipulated in the Regulation Legislation in force, ie in accordance with Article 130 paragraph (2) and Article 195 paragraph HIR (1) HIR. The legal consequences of the decision / deed peace is agreed and signed certificate from the then prevailing peace as the Law for the parties who made it, the parties should be required to fulfill and comply with the contents of the peace agreement set out in the peace deed. Deed of peace and binding have executorial strength. And a decision / deed of peace that has been agreed upon and signed by the parties to the dispute can not be filed an appeal. It is, as has been in accordance with the provisions set forth in Article 130 paragraph (3) HIR, which states that "Against such a decision can not be appealed